Strategi Pemberdayaan Kesejahteraan Keluarga di Kecamatan Galesong Utara Kabupaten Takalar dalam Upaya Penanganan Stunting Pada Masa Pandemi Covid-19 (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the strategy of Empowering Family Welfare in handling stunting in Bontolebang Village, North Galesong District, Takalar Regency. The research method used in this study is a qualitative research method with a descriptive research approach. The data collection techniques were obtained from observation, interviews with research informants as many as 12 people and documentation. The results showed that the PKK strategy in Bontolebang Village in the effort to deal with stunting had been carried out well based on the stages of the strategy process. The first stage is the formulation of strategies in the effort to deal with stunting by using institutional strategies and cross-sectoral approaches as well as strengthening Posyandu institutions. The second stage is the implementation of the strategy carried out in the form of the realization of programs such as the Germas, Gempita, and Gammara'na programs. The last stage is the evaluation stage of the PKK strategy in Bontolebang Village which includes reviewing the activities of internal and external factors that form the basis of the strategy. Internal factors are the utilization of existing resources, both human resources and facilities and infrastructure. As for external factors, namely the lack of allocation of funds issued by the government.